Characterization of core-shell oxide nanoparticles - Goossens, Eline (SLU/Department of Molecular Sciences, 2018)
The growing amount of applications of nanoparticles (NP) have led to concern for their possible harmful effect on human health and the leakage in the environment. Characterization and quantification of the content of NPs are of prime importance, especially methods to relate size, composition and morphology of the particles with the possibility of their detection and quantification.